EXTH-21. REPURPOSING GLIOBLASTOMA EXOSOMES AS PERSONALIZED MULTI-ANTIGENIC ANTI-TUMOR VACCINE. (5th November 2018) - Dusoswa, Sophie; Horrevorts, Sophie; Schetters, Sjoerd; Würdinger, Tom; Van Kooyk, Yvette; Garcia-Vallejo, Juan
Abstract: The composition of glial tumor derived exosomes (TEX) reflects plasma membrane and cytosol-derived proteins of the donor cell. Therefore, TEX form interesting candidates for anti-glioma skin dendritic cell targeted vaccination. Recent literature however, reports potent immune suppressive characteristics of TEX. TEX surface glycosylation may induce C-type lectin receptor triggering and/or cargo internalization thereby modifying the immunogenic/tolerogenic balance of the cellular immune response towards an immune suppressive phenotype. The aim of this study is to investigate whether we can repurpose TEX from immune suppressive vesicles towards immunogenic vehicles for multi-antigenic vaccination by de novo glycosylation of their surface. To this end, the surface glycosylation of TEX was carefully characterized by ELISA and electron microscopy. TEX uptake and downstream routing was assessed by imaging flow cytometry analysis. Our GBM-derived TEX were 50–200 nm in size and expressed high levels of CD63. The surface glycan profile of U251, U87, and GBM8-derived TEX was dominated by α-2, 3 and α-2, 6 sialic acid-capped N -glycans, high mannose glycans and truncated Tn-bearing O -glycans. These TEX appeared to have low affinity for DC-SIGN and MGL, but showed significant binding to Siglec-7 and Siglec-9. We developed a chemo-enzymatic glycan-modificantion protocol with the aim to replace Siglec ligands for DC-SIGN ligands in order to target them to skin resident dendritic cells for cross-presentation. Glycan-modified TEX, which had been introduced with a high affinity ligand for DC-SIGN, were efficiently taken up by human dendritic cells and fused with the endosomal pathway. In conclusion, repurposing glioma-derived TEX through de novo glycan-modification could provide a strategy for multi-antigenic anti-glioma vaccination.